An investigation of the development of an animated E-book: A gender difference approach. (November 2018) - Chen, Sherry Y.; Chang, Chih-Hung; Yang, Tzu-Chi; Wang, Jen-Hang
Abstract: Two empirical studies, i.e., preliminary study and main study, were included in this research. In the preliminary study, we developed a prototyped animated e-book system (PAES) that incorporated animation films into an e-book and examined how females and males reacted to design features provided by the PAES. The results from the preliminary study showed that gender differences significantly affected students' reactions to the PAES. Accordingly, the main study attempted to develop an animated e-book system (AES) that could accommodate gender differences based on the results from the preliminary study. The results from our main study showed that gender differences had no significant effects on students' learning performance and learning perceptions though females and males demonstrated different learning behavior. In other words, both females and males could equally benefit from the AES. Briefly, the major contribution of this research was to provide guidance on how to develop an animated e-book from a gender difference perspective. Such guidance can help designers to develop a versatile animated e-book that can support the needs and preferences of both females and males. Highlights: We investigated learners' reactions to an animated e-book. A gender difference Approach was applied to develop the animated e-book. A gender difference Approach was achieved by providing various tools and media. The needs and preferences of females and males were different.